Sensor modeling for portable Electrical Capacitance Tomography system using simulation by COMSOL Multiphysics - Elmy Johana, Mohamad, Dr.; Muhammad Afiq Zimam, Mohamed; Ruzairi, Abdul Rahim, Prof. Dr.; Leow, Pei Ling, Dr.; Mohd Hafiz Fazalul, Rahiman, Dr.; Khairul Hamimah, Abas; Salinda, Bunyamin (Innovative Computing, Information and Control (ICIC) International, 2013)
Link to publisher's homepage at http://www.ijicic.org/